Qualitative Parameters of the Colonic Flora in Patients with HNF1A-MODY Are Different from Those Observed in Type 2 Diabetes Mellitus - Sandra Mrozinska; Piotr Radkowski; Tomasz Gosiewski; Magdalena Szopa; Malgorzata Bulanda; Agnieszka H. Ludwig-Galezowska; Iwona Morawska; Agnieszka Sroka-Oleksiak; Bartlomiej Matejko; Przemyslaw Kapusta; Dominika Salamon; Maciej T. Malecki; et al. (Journal of Diabetes Research)
Background. Type 2 diabetes mellitus (T2DM) is determined by genetic and environmental factors. There have been many studies on the relationship between the composition of the gastrointestinal bacterial flora, T2DM, and obesity. There are no data, however, on the gut microbiome structure in monogenic forms of the disease including Maturity Onset Diabetes of the Young (MODY). Methods. The aim of the investigation was to compare the qualitative parameters of the colonic flora in patients with HNF1A-MODY and T2DM and healthy individuals. 16S sequencing of bacterial DNA isolated from the collected fecal samples using the MiSeq platform was performed. Results. There were significant between-group differences in the bacterial profile. At the phylum level, the amount of Proteobacteria was higher (p=0.0006) and the amount of Bacteroidetes was lower (p=0.0005) in T2DM group in comparison to the control group. In HNF1A-MODY group, the frequency of Bacteroidetes was lower than in the control group (p=0.0143). At the order level, Turicibacterales was more abundant in HNF1A-MODY group than in T2DM group. Conclusions. It appears that there are differences in the gut microbiome composition between patients with HNF1A-MODY and type 2 diabetes. Further investigation on this matter should be conducted.